SELF REGULATED LEARNING MAHASISWA DITINJAU DARI MOTIF MEMILIH JURUSAN - Yulfiana Rohmatin; Eva Latipah (Jurnal Pendidikan Agama Islam, 2015)
This study aims to describe self-regulated learning of students at the same time examine the relationship between self-regulated learning with student motivation in choosing majors. Subjects in this study were students majoring in Arabic Education (PBA) Faculty of Tarbiyah and Teaching UIN Sunan Kalijaga both men and women as many as 100 people. Interviews and scale self-regulated learning is used as an instrument in data collection.The results show: first, self-regulated learning of students as a whole are in the medium category (62%) with the highest aspect is the aspect of self-motivation (average value 20.43). Secondly, there is a significant positive relationship between self-regulated learning and motivation in choosing majors (r = 0.876 and p = 0. 004).